Composite materials and bovine cortical bone drilling: thermal experimental analysis - Fernandes, Maria (2016)
The bone drilling is a common procedure in orthopaedic surgery, mainly in the treatment of fractures and reconstructive surgery. The success of this surgeries is dependent of many factors and also in heat generation control during the drilling bone. The main concern in bone drilling are the mechanical and thermal damage of the bone induced by inappropriate parameters such as drill speed and feed-rate during surgical procedures. This paper studies the problem of generation heat in drilling process of composite materials, with similar mechanical properties to the human bone, and in bovine cortical bone. The main goal was study the evolution of temperature through the different experimental methodologies using different drilling parameters. It was concluded when the drill speed and feed-rate are higher the bone temperature increase is lower. The results of temperature in the drilling process of composite material or bovine bone were compared and were found a good agreement with both.